1990
DOI: 10.1111/j.1570-7458.1990.tb01346.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of starvation on development and reproductive potential of apterous virginoparae of vetch aphid, Megoura viciae

Abstract: Apterous virginoparae of Megoura viciae Buckton starved during the fourth instar lost weight but nevertheless completed their development, showing that growth and development could proceed independently. Their weight at the end of starvation was a function of initial weight. Aphids used considerable amounts of lipid during starvation, and if allowed to feed on becoming adult showed a delayed onset to reproduction. Starvation in the fourth instar arrested embryogenesis, and in small aphids resulted in degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
2
15
0
2
Order By: Relevance
“…1f), changes in resource allocation within the developing aphid (perhaps associated with nutrient stress (e.g. Brough & Dixon, 1990) do not explain these results. Aphids reared at elevated CO 2 and/or O 3 may either have been unable to maintain embryo maturation once their initial complement of mature embryos were born, or have resorbed the youngest undifferentiated embryos in response to low host plant quality (e.g.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…1f), changes in resource allocation within the developing aphid (perhaps associated with nutrient stress (e.g. Brough & Dixon, 1990) do not explain these results. Aphids reared at elevated CO 2 and/or O 3 may either have been unable to maintain embryo maturation once their initial complement of mature embryos were born, or have resorbed the youngest undifferentiated embryos in response to low host plant quality (e.g.…”
Section: Discussionmentioning
confidence: 84%
“…Because both CO 2 and O 3 affect plant quality, it may not be possible to make reliable predictions about the future fecundity of herbivorous insects without directly measuring the number of offspring produced. Similarly, recent studies (Bezemer et al , 1999; Percy et al , 2002) suggest that the performance of individual herbivores may not predict population responses to elevated CO 2 or O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population may react and adapt to stressful conditions by developing biological strategies for acclimatization or by evolving more resistant macromolecules to retain functional efficiency in the altered environment (Karan & David, 2000). Many studies have reported that the ability to arrest or resorb oocytes in insects is a reproductive strategy that enables their shortterm tolerance of a lack of food, a lack of oviposition sites, or other stresses (reviewed in Bell & Bohm, 1975;Brough & Dixon, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Starved aphids adopt a quite different strategy of resorption. The smallest embryos were resorbed and the largest embryo in each ovariole continued to mature, which to a limited extent, enables it to adjust its reproductive biomass during starvation (Ward & Dixon, 1982;Brough & Dixon, 1990). Leather et al (1983) reported that starvation could cause a decreased total fecundity in apterous Aphis fabae Scopoli adults.…”
Section: Introductionmentioning
confidence: 99%